2016
DOI: 10.1002/j.0022-0337.2016.80.12.tb06233.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Sequence of Preclinical Dental Crown Type Preparations Affect Evaluation Scores?

Abstract: Preclinical dental students must demonstrate aptitude in the preparation of teeth for treatment with several types of fixed dental prostheses. The optimal sequence of instruction and examination of these crown preparations in preclinical fixed prosthodontics is unknown. The aim of this study was to determine if grading scores by faculty and students were affected by changing the sequence of crown type preparations. Practical exams of two successive student cohorts (n=89 in 2014; n=92 in 2015) at one U.S. denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Fixed prostheses are one of the main courses in dentistry, and dentists deal with them a lot in their daily practices (15). Students should be trained in dental materials, impression techniques, and crown preparation principles before entering the clinical stages (15)(16)(17). Some studies have reported the relationship between student performance in preclinical and clinical courses.…”
Section: Introductionmentioning
confidence: 99%
“…Fixed prostheses are one of the main courses in dentistry, and dentists deal with them a lot in their daily practices (15). Students should be trained in dental materials, impression techniques, and crown preparation principles before entering the clinical stages (15)(16)(17). Some studies have reported the relationship between student performance in preclinical and clinical courses.…”
Section: Introductionmentioning
confidence: 99%